Effect of Al addition to rapidly solidified Mg-Cu-Rare Earth alloys - Rozenberg, S; Audebert, F; Galano, M; Ogando, I; Mendive, C (Universidade Federal de São Carlos, 2016)
Rapidly solidified Mg based alloys are of interest for industrial applications as a structural material and for hydrogen storage. Mg-Cu-Rare Earth alloys have shown high glass forming ability; full amorphous structure with thickness of mm size can be obtained within these systems. However, their brittle behavior limits their industrial applications. In the present work, the Al effect in substitution of Cu in the Mg65Cu25MM10 (at%, MM: mischmetal) was studied. Samples up to 15at% Al were prepared by splat cooling and their microstructure, stability and mechanical properties were characterised. The crystallization temperature increases with the Al addition; the amorphous phase with different Al content has a Young's modulus of ~55GPa; the microhardness increases with the Al content in the amorphous and crystallized samples and the fracture of the alloy containing 10at% Al showed ductile vein patterns characteristics of ductile metallic glasses. The partial Cu substitution by Al can improve the stability and mechanical properties of the amorphous Mg65Cu25MM10 alloy.